Geliat Komik Indonesia - Hafiar, Hanny; Kurniadi, Oji (Mediator, 2008)
The expectation to send the victory of Indonesian comics as well as in 1960 is getting wider. The rising of Indonesian youth comic maker through the big or Indy publishing house is one of the indications. But the expectation would be blown by a lot of problems. The problems are the quality of drawing and story line from young comic maker that still adopts Japanese style, the existence of porn illegal comics decreases attention of reader to read local comics, suboptimal controlling of government to illegal publishing and the pride less of our society to their own products. Teamwork from a lot of element with each portion is a must to handle the problems, so we can hope that foreign comic which is some time inappropriate with our culture not dominate Indonesian comics industry anymore.